The Galician Dictionaries and the Operators and Discourse Markers of Contact Control - Rodríguez Guerra, Alexandre (Madrygal. Revista de Estudios Gallegos, 2018)
This contribution researches the presence of a series of discourse markers in seven Galician dictionaries of distinct format and size. Particulary, it explores two groups of markers: (i) operators and (ii) contact control. From the proposal of Freixeiro Mato for the Galician, we review these units, we verify their inclusion in the dictionaries selected and we analyze the discursive meanings associated to these two groups of discourse markers. In this sense, there are more operators than contact control markers. We also examine all the definitions, the parts of speech and the examples. The contrastive analysis of the results indicates that the two basic types of definition are the synonymic conceptual (simple and complex) and the functional. The choice of a particular model of definition depends on the type of discourse marker selected. The word class associated to these units is centered around two basic poles: the first is the absence of categorical identification, the second privileges some of the invariable categories. Finally, also we observe a different amount of examples in the seven dictionaries.
Keywords: Galician; Dictionaries; Discourse Markers; Operators; Contact Control.